Elaboración y aplicación de un folleto que contenga experimentos infantiles para desarrollar la investigación científica en los niños de 4 a 5 años de la Unidad Educativa San José “La Salle” en el periodo 2010-2011. - Ávila Taco, Mirián Verónica (2011)
The present work was carried out with the aim at developing scientific investigation through the elaboration of a booklet that contains experiment with children to be applied in the teaching-learning process for the children of the San José “LA SALLE” educative unit by means of workshops of: experiments on children; such as the wonderful seed, secret of the tongue, layouts, corroded apple, the spy eye, you before your eyes, among others.